1973
DOI: 10.2307/2534085
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Labor Market for Black Americans, 1948-72

Abstract: Changes i n t he Labor Market for Black Americans, 1948-72 THE ECONOMIC STATUS OF BLACK AMERICANS has changed greatly over the past two decades. In some aspects of market position-years of school completed, occupational attainment, and income-blacks have risen relative to whites. Other measures of economic status-employment, unemployment, and labor force participation-reveal marked black-white differences in annual and longer-run patterns of change. Some groups of black workers-women and college-trained men-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(117 citation statements)
references
References 0 publications
3
113
0
1
Order By: Relevance
“…Similar to the earlier work of Freeman (1973), Cattan (1988) and Defreitas (1986) each document the growing presence of Hispanics in the U.S. work force in the 1980s.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Similar to the earlier work of Freeman (1973), Cattan (1988) and Defreitas (1986) each document the growing presence of Hispanics in the U.S. work force in the 1980s.…”
Section: Introductionsupporting
confidence: 60%
“…The ratio of black-to-white unemployment rates has been roughly 2-to-1 for several decades since the 1950s (Fairlie andSundstrom 1997, 1998). In Richard Freeman's (1973) classic study of racial patterns of labor market status from 1948 to 1972, he found that the level of employment for blacks was more volatile than that for whites and that the unemployment rate for blacks rises more than that for whites in percentage points when the economy weakens. Based on these findings, Freeman (1973) proposed a "last in, first out" pattern of black employment over the business cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among women, blacks were found to face a 106 percent greater chance than whites of facing safety hazards and a 91 percent greater chance of facing health hazards. These figures exceed the race-related differences in earnings levels during this period (Freeman 1973).…”
Section: Equal Opportunity and Occupational Healthmentioning
confidence: 62%
“…One possibility is that in slack labor markets long queues of job applicants make it less costly for employers to discriminate, because they are not passing up qualified older workers in favor of less-qualified younger workers; this argument goes back to Ashenfelter (1970) and Freeman (1973), and was recently considered by Biddle and Hamermesh discrimination protections. One possibility is that because stronger state age discrimination laws impose constraints on employers, there could be more "pent-up demand" for age discrimination in these states, which firms act on during a sharp downturn.…”
Section: Introductionmentioning
confidence: 99%